Novel Coronavirus: A Newly Arranged Mini-Review - Siwani Devi; Kishan Tripathi; Mohammad Mukim; Vidhi Jain; Nesar Ahmad; Noorul Hasan; Prashant Kumar Singh; Mohammad Khalid (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was originally known as a virus that infects animals and rarely can be transmitted to humans in large populations, is now transformed into one of the most feared pandemics causes worldwide. Infection by a virus that is officially known as COVID-19 has caused global concern mainly due to the number of deaths caused. Since it was first reported in Wuhan, China in December 2019, now COVID-19 has spread to almost all parts of the world with a very rapid spread rate. The main symptom of this infection is a respiratory disease accompanied by other symptoms that resemble flu-like illness. Everyone can suffer from COVID-19, but the elderly, toddlers, pregnant women, and people with certain diseases and disorders of the immune system show more severe symptoms. The disease is transmitted through inhalation or contact with droplets, where the incubation period ranges from 2 to 14 days. Until now, specific therapy to treat COVID-19 has not been found, with preventive measures taken to control its spread. In this mini-review, we will explain important information related to COVID-19.